2016
DOI: 10.1177/2168479016628301
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Opinions on Existing and Proposed Australian Over-the-Counter Medicine Labeling Strategies in Comparison With the Standardized US Drug Facts Label

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A further two label formats were developed by applying good information design and findings from a consumer needs analysis. 21, 22 An existing OTC label for a diclofenac product available for purchase in Australia (Voltaren® Rapid 25 23 ) was also selected as a comparator label. In order to determine whether these label formats were fit-for-purpose, they…”
Section: Methodsmentioning
confidence: 99%
“…A further two label formats were developed by applying good information design and findings from a consumer needs analysis. 21, 22 An existing OTC label for a diclofenac product available for purchase in Australia (Voltaren® Rapid 25 23 ) was also selected as a comparator label. In order to determine whether these label formats were fit-for-purpose, they…”
Section: Methodsmentioning
confidence: 99%
“…Research demonstrates that consumer interpretation is inconsistent and incomplete when reading currently available medications information such as packaging and CMIs . Australian research has been undertaken to investigate alternative written materials to provide medications information, although alternatives are not yet readily available in practice . This research identified approaches to improve consumer resources to assist medications users to comprehend and identify pertinent information .…”
Section: Fundingmentioning
confidence: 99%
“…Even so, both researchers and regulators guiding the development of OTC label formats tend to focus their efforts on latestage processing (comprehension). Historically, comprehension studies have utilized surveys and questionnaires (Murty & Sansgiry, 2007;Wawruch et al, 2013); guided interviews (King et al, 2011;Martin-Hammond et al, 2015;Tong et al, 2015Tong et al, , 2017; and focus groups (King et al, 2011;Tong et al, 2016) in which participants are asked to evaluate which type of warning text or display would be more effective.…”
Section: Introductionmentioning
confidence: 99%